If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -7) = 16 Reorder the terms: 8(-7 + x) = 16 (-7 * 8 + x * 8) = 16 (-56 + 8x) = 16 Solving -56 + 8x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 8x = 16 + 56 Combine like terms: -56 + 56 = 0 0 + 8x = 16 + 56 8x = 16 + 56 Combine like terms: 16 + 56 = 72 8x = 72 Divide each side by '8'. x = 9 Simplifying x = 9
| 9(x-3)=54 | | 7(x-2)=14 | | 5y^2-16y-52=0 | | 6(4+x)=36 | | 5(x+6)=100 | | X^6-72x^3+512=0 | | x^4-x-1=0 | | 12x^2-240x+900=0 | | 10x+80=180 | | 2y^2+3y-6.875=0 | | 3(5)=33 | | 19-3(m+4)+4m=42-18 | | 5x^3-2x^2+45x-18=0 | | 2(-5x+7)= | | 5x^3-2x^2-45x-18=0 | | 2x-3(-7x-8)=114 | | 5x^3+2x^2+45x-18=0 | | 2-(-6+3x)= | | 4(2-3x)= | | -4x+2(-x-9)=24 | | -(-6x+3)= | | -4(x+2)=-20 | | 8b^2-15b-2=0 | | 36=4(2x-3) | | 12=4x+3(3x+19) | | -2(20+4x)=-24 | | -(3x-2)=-10 | | 2(10-3x)=-28 | | 12+(3-x)=7 | | 7x+2(-6x-17)=-148 | | -8=-12-(6-x) | | 20-4(6-x)=4 |